Overlapping hydration shells in salt solutions causing non-monotonic Soret coefficients with varying concentration. Issue 44 (4th November 2022) - Mohanakumar, Shilpa; Kriegs, Hartmut; Briels, W. J.; Wiegand, Simone
Abstract : We develop an intuitive picture that overlapping hydration shells in salt solutions cause non-monotonic Soret coefficients with varying concentration. Abstract : We investigate the thermodiffusive properties of aqueous solutions of sodium iodide, potassium iodide and lithium iodide, using thermal diffusion forced Rayleigh scattering in a concentration range of 0.5–4 mol kg −1 of solvent, large enough to deal with associated salts, and a temperature range of 15 to 45 °C. All systems exhibit non-monotonic variations of the Soret coefficient S T with concentration, with a minimum at one mol kg −1 of solvent in all three cases. We take this as an indication that the relevant length and energy scales are very similar in all cases. On this basis we develop an intuitive picture in which the relevant objects are the fully hydrated salt molecules, including all water molecules that behave differently from bulk water. Preliminary, somewhat sketchy calculations indicate that indeed Soret coefficients begin to rise beyond concentrations where the fully hydrated particles are randomly close packed. Indications are given as to why the model will fail at large concentrations.